The Truth of Monotheism in Egypt Throughout Historical Epochs - Mousa, Ibrahim Dirbas (Journal of Ecohumanism, 2024)
This study, entitled “The Truth of Monotheism in Egypt Throughout Historical Epochs”, I clarified monotheism in Egypt starting from ancient historical eras. This includes the era of Prophet Idris (Peace Be Upon Him), who is considered the grandfather of Prophet Noah (Peace Be Upon Him). In fact, Prophet Seth (Peace Be Upon Him) was his great-grandfather. Then I documented the features of true monotheism during the time of the Sheikh of Prophets and Messengers, our master Abraham (peace and blessings be upon him). This was followed by his grandchildren, represented by Prophet Jacob (Peace Be Upon Him) and his children and grandchildren (Peace Be Upon Them). I then addressed this monotheistic Truth in the Islamic era. This begins with the letter sent by the Prophet of Islam, Muhammad (Peace Be Upon Him), through the companion Amr ibn Balta'a to the ruler of Egypt at that time, King Muqawqis. I divided my research into an abstract in both Arabic and English, followed by a table of contents, then an introduction, and then two sections as follows. The first section: Definitions, which includes three topics. The second section: Prophets and Messengers (Peace Be Upon Them) in Egypt, which includes four topics. Then the conclusion, the most important findings and recommendations, and the most important sources and references.